1992
DOI: 10.1177/016327879201500304
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and Accuracy of Resident Evaluations of Surgical Faculty

Abstract: This study examines the reliability and accuracy of ratings by general surgery residents of surgical faculty. Twenty-three of 33 residents anonymously and voluntarily evaluated 62 surgeons in June, 1988; 24 of 28 residents evaluated 64 surgeons in June, 1989. Each resident rated each surgeon on a 5-point scale for each of 10 areas of performance: technical ability, basic science knowledge, clinical knowledge, judgment, peer relations, patient relations, reliability, industry, personal appearance, and reaction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 4 publications
0
22
0
1
Order By: Relevance
“…performance evaluation gives similar ratings across all dimensions rather than distinguish amongst single dimensions (Risucci et al 1992;Williams et al 2003). In contrast to consultants, surgical residents and interns can spend significant amounts of time teaching and directly supervising medical students in a wide variety of different clinical settings (Lowry 1976;Pelletier & Belliveau 1999;Minor & Poenaru 2002;Whittaker et al 2006).…”
Section: Practice Pointsmentioning
confidence: 99%
“…performance evaluation gives similar ratings across all dimensions rather than distinguish amongst single dimensions (Risucci et al 1992;Williams et al 2003). In contrast to consultants, surgical residents and interns can spend significant amounts of time teaching and directly supervising medical students in a wide variety of different clinical settings (Lowry 1976;Pelletier & Belliveau 1999;Minor & Poenaru 2002;Whittaker et al 2006).…”
Section: Practice Pointsmentioning
confidence: 99%
“…Cohen, MacRae, and Jamieson (1996) found that medical students evaluating their surgery instructors achieved an intraclass correlation of only 0.65. Similarly, Risucci et al (1992) found that interrater correlations only averaged between 0.62 and 0.64. Donnelly and Woolliscroft (1989) found intraclass class reliabilities for 12 evaluation items ranged from a low of 0.64 to a high of 0.82.…”
Section: Reliability and Agreementmentioning
confidence: 86%
“…Indeed, the judicious use of subjective instruments may be quite reliable, even if less standardized than a national examination, and previous subjective studies of surgeon evaluations have shown good internal consistency. 25,26 This applies to the present study as well as the internal measurements used within a program for resident education.…”
Section: Discussionmentioning
confidence: 98%